Research on 3D Development Characteristics of Water-Conducting Fractured Zone Based on Field Measurement - Feng, Dong; Hou, Enke; Wang, Shuangming; Xie, Xiaoshen; Yuan, Feng; Guo, Liangliang; Wang, Gang; Xie, Yongli; Chen, Zhen (Frontiers in Earth Science, 2022)
With the large-scale mining of coal resources in western China, coal resources are gradually shifting from shallow to deep mining. In coal seam mining, the overlying rock water-conducting fractured zone (WCFZ) is the main factor causing mine water damage and water resource damage. Accurately grasping the development height of the water-conducting fissure zone is the key to the prevention of water hazards and the protection of water resources in medium–deep coal seams. In this study, the 3D development form of the WCFZ in the middle and deep coal seam mining is studied by the integrated method of drilling and 3D seismic survey, taking the first mining face of Xiaobodang No.1 mine in Yushen such that the height of the WCFZ measured by drilling is 81.50–177.07 m. The height of WCFZ development in the 3D seismic survey was 79.83–178.03 m, and the morphology of the WCFZ was saddle-shaped. This study provides methodological guidance for predicting the 3D morphology and developmental characteristics of the WCFZ. The results obtained are of great significance for the safe, green, and efficient mining of coal seams in medium and deep buried ecologically fragile environments.